Project Report on Asset Tracking of A Futuristic Soldier - SAI SWAROOP M, SANJAY KUMAR P, and VENKATESH PRASAD C (2013)
INTERNAL GUIDE : Krishnamoorthy EXTERNAL GUIDE : Prayoona Valsalan and Naveen Kumar G N USN NO : 1MJ09EC056, 1MJ9EC060, 1MJ09EC064 1MJ09EC075 CARRIED OUT AT : MVJ College Of Engineering Bangalore-560067 ACC NO : PR1982
Keywords: Tracking of A Futuristic Soldier